2023
DOI: 10.3390/soilsystems7020043
|View full text |Cite
|
Sign up to set email alerts
|

Process-Based Crop Models in Soil Research: A Bibliometric Analysis

Abstract: Different types of soil data are used in process-based crop models as input data. Crop models have a diverse range of applications, and soil research is one of them. This bibliographic analysis was conducted to assess the current literature on soil-related applications of crop models using two widely used crop models: Agricultural Production Systems Simulator (APSIM) and Decision Support System for Agrotechnology Transfer (DSSAT). The publications available in the Scopus database during the 2000–2021 period we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Five locations with observed soil data were used in this study, as shown in Figure 1 (Puttalam, Katunayake, Galle, Hambantota, and Badulla). The observed soil data were obtained from the SRICANSOL project [28][29][30][31], which is the most up-to-date and comprehensive soil database in Sri Lanka. These locations were selected to cover all three climate zones of the country: WZ, DZ, and IZ.…”
Section: Soil Data Collectionmentioning
confidence: 99%
“…Five locations with observed soil data were used in this study, as shown in Figure 1 (Puttalam, Katunayake, Galle, Hambantota, and Badulla). The observed soil data were obtained from the SRICANSOL project [28][29][30][31], which is the most up-to-date and comprehensive soil database in Sri Lanka. These locations were selected to cover all three climate zones of the country: WZ, DZ, and IZ.…”
Section: Soil Data Collectionmentioning
confidence: 99%